The concept of housing as it relates to finance (2017)
The conceptual frame work of housing in this work bothers on Neighbourhood unit principle that has to do with supply of services of higher and lower orders to its inhabitants. On the other and housing demand reflected the price and the ability to pay and the product must be available in terms of supply. It was discovered that the minimum paid worker’s allowance cannot meet the requirement for obtaining housing in Nigeria. The uncertainty of the economic situation did not promote housing provision, inadequate budgetary allocation to housing has led to decrease and poor quality and quantity of housing delivery. The data on the disbursement and repayment and the number of housing provided as at January 2012 was highlighted. It was suggested that the financial structure of Federal Mortgage Bank of Nigeria should be modified to accommodate housing cooperatives, housing associations, credit union, government machinery, saving banks and designated financial institution for housing that will cater for different categories of people.